Pengabdian Kepada Masyarakat: Peningkatan Digitalisasi Marketing untuk Pengembangan Desa Wisata Kemetul - Angga Prastiyo; Dwi Nurrahmawati (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
The Village Government & managers of Kemetul Tourism Village do not understand much about digitization transformation, digitization opportunities, and technological innovation in the tourism sector. Observation preparation is the first step to dig deeper into the existing problems. Training for the Village Government & Management of Kemetul Tourism Village to understand the challenges and opportunities of digitalization marketing in the tourism sector. Practice and apply digitalization marketing for the development of tourism villages. With the understanding and training digitalization has the potential to drastically change the tourism industry, allowing better knowledge management, faster innovation, and better data security while reducing operational time. In addition to providing understanding, there is also a need for training in tourism service technology innovation. Many types of tourism service technology make it easier for managers such as the use of social media and websites that can be accessed in the form of websites and smartphone applications.